The association of late carpal tunnel syndrome with carpal misalignment following distal radius fracture in old Jordanian women - Jbarat, Ashraf; Obeidat, Mohammad; Abu Qa’oud, Moayad; Jaradat, Mahdi; Al-Oun, Mohammad (International Journal of Research in Orthopaedics, 2023)
Background: Late carpal tunnel syndrome following distal radius fracture is a frequent hazard especially after conservative management. Objective was to assess the association of radiological carpal alignment with the intensity of late carpal tunnel syndrome in old Jordanian women during 1 year of distal radius fracture. Methods: Our retrospective investigation recruited 100 women, aged more than 50 years with unilateral distal radius fracture managed conservatively during one year of the fracture at Royal Jordanian Rehabilitation center, Jordan, between January 2021 to April 2023. Participants were split into 2 groups. Group I comprised of 50 patients with clinical features of late carpal tunnel syndrome (nocturnal or diurnal) and group II comprised of 50 women without clinical features. CTS-6 assessment tool score (1-6) was recorded to evaluate the intensity of the condition. Electrophysiological and radiological evaluation were performed to record carpal alignment. Student t-test was used to assess the variables. Results: There was a remarkable discrepancy between groups in terms of the radiological variables of carpal alignment (The average of radio-capitate distance, volar tilt and volar prominence height were: -10.69 mm, -19.89 D angle and 1.45 mm, respectively in group I). There was a positive association between reduction in the variables of carpal alignment and the intensity of late CTS. Volar tilt was positively engaged in the late CTS. The threshold of the volar tilt was -19.41 D angle (p<0.005). Conclusions: Modification of the carpal tunnel following distal radius fracture with carpal dorsal misalignment leads to late CTS. Reducing volar tilt and volar prominence height and radio-capitate distance are the main remarkable independent anticipators of late CTS in non-surgically treated distal radius fracture.